Green IT: cybersecurity cost or benefit?. (11th January 2022) - Proctor, Tony
Abstract: Tony Proctor CITP, Principal Lecturer at the University of Wolverhampton and Emily Proctor, Post-Graduate Student in International Security, discuss whether green IT and cybersecurity can be mutually beneficial.